Culinária típica e identidade regional: a expressão dos processos de construção, reproduçãoe reivenção da mineiridade em livros e restaurantes de comida mineira - Luciana Patricia de Morais (2004)
M.A. dissertation in Social History of the Culture, that tried to understand the plasticity of the regional identity of Minas Gerais, starting from the following sources: books and restaurants related to the regional typical cookery. The work was divided in three chapters. First, the focus was the institution and consolidation of the history of feeding as a field for interdisciplinary study. Soon after, the intention was to signal, in the consulted sources, elements that enable to speak of the identity as an imaginary construction and as cultural practice that allows an ideological speech as private appropriations, reinventions. The cookery was taken as form of expression of the culture of Minas Gerais and we tried to show how books and restaurants of typical cookery can transmit it. In this movement, the global phenomenon was shown as important variable for the understanding of the reinforcement of the association between the identity and the cookery of Minas Gerais starting from the years of 1970, with unfoldings up to the present time. The insert of the identity of Minas Gerais in the historical dynamics contributes to the development of the debate between historians and social scientists.